A Survey of Gastrointestinal Parasites of Domestic Cats (Fells catus) in Kuching, Sarawak. - Low, Suet Ee (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Domestic cats (Fells catus) are known to be commonly infected with parasites because of their habit of roaming freely, especially stray cats. Up until now, there are still lack of information and published papers regarding parasites of cat in Sarawak. Main objective of this study was to investigate and compare the gastrointestinal parasites of house-owend and stray cats. A total of 60 faecal samples were collected from domestic cats in Kuching, in which 30 samples from house-owned and stray cats each. Concentration technique such as centrifugal floatation and sedimentation were used for the examination of gastrointestinal parasites. Overall prevalence of gastrointestinal parasites in all cats was 46.67% (28/60) in this study, where gastrointestinal parasite prevalence of house-owned cats was 33.33% (10/30) and stray cats was 60% (18/30). Detected nematode species includes Ancvlostoma spp. (30%). Toxocara spp. (10%) and Toxascaris leonina (5%) while recovered flatworm (18.83%) includes 17 different types of morphologies. Isospora spp. was the only protozoan parasite species recovered in this study with the prevalence of 6.67%. There was no significant difference on species diversity of gastrointestinal parasite between house-owned and stray cats.